The best possibility of the bound for the Kantrovich inequality and some remarks. Issue 4 (1997) - Tsukada, M.; Takahasi, Sin-El
Abstract : The necessary and sufficient condition for equality to be attaind in the Kantrovich inequality is given and applied to an inequality of normal operators on Hilbert spaces.